2021
DOI: 10.1016/j.jns.2021.117610
|View full text |Cite
|
Sign up to set email alerts
|

Neurological comorbidities and COVID-19-related case fatality: A cohort study

Abstract: Background: Neurological involvement in Coronavirus disease-2019 (COVID-19) is widely recognized. However, the role of pre-existing neurological comorbidities in modulating COVID-19-related mortality still remains unclear. This cohort study evaluates the COVID-19-related case fatality rate (CFR) of patients with pre-existing neurological diseases. Methods: We retrospectively evaluated all patients consecutively admitted to our hospital with a diagnosis of COVID-19 between March and April 2020. We used a multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Consistently with other reports, we found a COVID-19-associated crude case fatality rate of 31%, with a more than double risk of dying in dementia patients compared to the general population of the same age and gender [38,39]. Our analysis revealed a strong association between presence of symptoms at…”
supporting
confidence: 92%
“…Consistently with other reports, we found a COVID-19-associated crude case fatality rate of 31%, with a more than double risk of dying in dementia patients compared to the general population of the same age and gender [38,39]. Our analysis revealed a strong association between presence of symptoms at…”
supporting
confidence: 92%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been linked to abnormalities in the central nervous system such as the loss of smell and taste, cognitive decline, delirium, cerebrovascular accidents, neuronal autoimmune illnesses, and psychiatric disorders [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. However, the heterogeneity of symptoms remains puzzling [ 1 , 3 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterogeneity of symptoms remains puzzling [ 1 , 3 , 7 , 8 , 9 , 10 ]. The development of these abnormalities often occurs within two days from the onset of symptoms [ 1 , 5 , 7 , 11 , 12 ]. In addition, an increasing number of survivors suffer from long-term neurological sequela [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are also consistent with a recent study by Romagnolo et al, who stated that cerebrovascular disease and cognitive impairment are determinants of COVID-19 severity [ 36 ]. Another article by the same authors demonstrated that chronic neurological conditions, especially neurodegenerative diseases, increase lethality in COVID-19 cases [ 55 ]. In addition, Du et al reported a 2.4-fold increase in mortality risk in patients with cerebrovascular or cardiovascular disease, although they did not specify the distinction between these two conditions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%